Health advocacy by nurses in the Family Health Strategy: barriers and facilitators - Aline Belletti Figueira; Edison Luiz Devos Barlem; Simone Coelho Amestoy; Rosemary Silva da Silveira; Jamila Geri Tomaschewski-Barlem; Aline Marcelino Ramos
ABSTRACT Objective: Identify the barriers and facilitators of health advocacy to users delivered by nurses from the Family Health Strategy. Method: Qualitative study carried out with nurses from the Family Health Strategy of a city in the south of Brazil. Study participants were 15 nurses, who were interviewed. The content of the interviews was recorded, transcribed and analyzed in the light of the discursive text analysis. Results: Two categories emerged, one about the lack of organization at the workplace, bureaucracy and limitations to professional work in health environments, and another about the facilitating aspects to exercise advocacy both individually and collectively. Conclusion: When nurses, provided with technical, scientific and relational knowledge, are empowered to make decisions, they are not only supported by other professionals at work but also develop actions of health advocacy to users, thus qualifying the care delivered.